2019
DOI: 10.3389/fmicb.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiome Diversity in Traditionally Prepared Starters for Alcoholic Beverages in India by High-Throughput Sequencing Method

Abstract: Chowan, dawdim, humao, hamei, khekhrii, and phut are sun-dried starters used for preparation of alcoholic beverages in North East regions of India. We attempted to profile the mycobiome community in these starters by high-throughput sequencing (HTS) method. All fungal populations were found to be restricted to Ascomycota (67–99%), Zygomycota (0.7–29%), Basidiomycota (0.03–7%), and Chytridiomycota (0.0003%). We found 45 core operational taxonomic units (OTUs) which were universally present and were further weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
(119 reference statements)
1
27
0
Order By: Relevance
“…Drinking of cereal-based mild to strong alcoholic beverages produced by traditionally prepared amylase and alcoholproducing starters has been a traditional food culture of the ethnic people from the North East states of India for centuries. Traditionally prepared dry starters have consortia of co-existed microbiota containing filamentous molds, yeasts, and bacteria and are crudely sub-cultured through a "backslopping" process by traditional starter-makers Tamang and Sarkar, 1995;Tamang et al, 2007;Sha et al, 2018Sha et al, , 2019, for alcohol production by the Indian people. The pH of traditionally prepared dry starters from India were slightly acidic in nature, perhaps due to accumulation of metabolic organic acids (Ma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Drinking of cereal-based mild to strong alcoholic beverages produced by traditionally prepared amylase and alcoholproducing starters has been a traditional food culture of the ethnic people from the North East states of India for centuries. Traditionally prepared dry starters have consortia of co-existed microbiota containing filamentous molds, yeasts, and bacteria and are crudely sub-cultured through a "backslopping" process by traditional starter-makers Tamang and Sarkar, 1995;Tamang et al, 2007;Sha et al, 2018Sha et al, , 2019, for alcohol production by the Indian people. The pH of traditionally prepared dry starters from India were slightly acidic in nature, perhaps due to accumulation of metabolic organic acids (Ma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some traditionally prepared starters from North East India have been microbiologically analyzed in earlier works and several species of yeasts (Tsuyoshi et al, 2005;Jeyaram et al, 2008Jeyaram et al, , 2011Sha et al, 2017Sha et al, , 2018Sha et al, , 2019 and bacteria (Tamang et al, 2007;Pradhan and Tamang, 2019) were reported. However, detailed taxonomical studies of filamentous molds isolated from traditionally prepared dry starters from North East India have not been reported yet, except for marcha (Tamang et al, 1988;Tamang and Sarkar, 1995;Sha et al, 2017Sha et al, , 2019, thiat (Sha et al, 2017(Sha et al, , 2019, amou, perok-kushi (Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted gene amplicon sequencing has revolutionized the eld of food microbial ecology [12,13,14,15,16]. High-throughput sequencing methods have been also widely used in many naturally fermented products of North-East India [17,18,19,20]. Naturally fermented milk (NFM) products are popular food items in daily diets of ethnic people of Arunachal Pradesh and Sikkim in India which includes dahi, mohi, gheu, soft-chhurpi, hard-chhurpi, dudh-chhurpi, chhu, somar, maa, philu, shyow, mar, chhurpi/churapi, churkam and churtang/chhurpupu [21].…”
Section: Introductionmentioning
confidence: 99%